Step-by-step dacryocystorhinostomy for beginners: An expert′s view - Shrikant Deshpande; Anjaneya Agashe; Abhinav Loomba; Neha Dhiware (Journal of Clinical Ophthalmology and Research, 2014)
Chronic dacryocystitis occurs usually due to obstruction of lacrimal passage at the junction of the lacrimal sac and the nasolacrimal duct or within the bony nasolacrimal duct. Reconstruction of the lacrimal passages in such cases can be achieved by several surgical techniques, although external dacryocystorhinostomy (DCR), proposed by Ohm and by Dupuy-Dutemps and Bourguet in 1921, is still the most successful operation. Despite ease and decreased morbidity of endonasal DCR, external DCR is procedure of choice as it is more successful. Several ophthalmologists fear performing DCR because of bleeding and unfamiliarity of structure. This article tries to provide few tips to make DCR easy and stress-free. Proper case selection, pre-operative workup and adequate exposure go a long way in making DCR stress-free and successful. Excessive bleeding, a common hindrance in DCR surgery can be successfully tackled by proper positioning of patient, use of adrenaline, suction, and adjustment of nasal pack.